Bootstrap and Jacknnife resampling in reliability: case exponential and Weibull - Ramírez-Montoya, Javier; Osuna-Vergara, Ignacio; Rojas-Mora, Jessica; Guerrero-Gómez, Stalyn (Universidad Pedagógica y Tecnológica de Colombia, 2016)
In this paper the resampling methods bootstrap-t, Jackknife delete I and delete II, are compared using the non-parametric estimators Kaplan-Meier and Nelson-Aalen, frequently used in the practice, taking into account different percentages of censorship, sample sizes and times of interest. The comparation is carried out by simulation, using the mean square error.